2005
DOI: 10.1111/j.1439-0426.2005.00689.x
|View full text |Cite
|
Sign up to set email alerts
|

Abundance and night-time habitat use patterns of Ponto-Caspian gobiid species (Pisces, Gobiidae) in the littoral zone of the River Danube, Hungary

Abstract: We examined the abundance and meso-habitat use of gobiid species during both day and night along 43 stretches (500-m long) of the littoral zone at five locations of the Middle Danube, Hungary, in spring and in summer 2004. Electrofishing catch per unit effort sampling revealed significantly higher relative densities at night than during the day. Gobiids occupied all the available habitats encountered during sampling. Habitat-abundance relationships from night-time samples revealed that the two most abundant sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
71
3
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(86 citation statements)
references
References 35 publications
8
71
3
4
Order By: Relevance
“…Assuming that shelter occupancy differs between day and night, not only season but also time of the day should influence the magnitude of interference between the bullhead and both goby species. Bottom-dwelling fishes such as bullheads and some Ponto-Caspian gobies are usually nocturnal, seeking a hiding place during the day and being most active at dusk or at night (Tomlinson and Perrow 2003;Erös et al 2005;Johnson et al 2008;Gaygusuz et al 2010;Grabowska et al 2016). On the other hand, shelter occupancy by the monkey goby did not differ between night and day, which corroborates the lack of a clear diel pattern of its foraging activity (Grabowska et al 2009).…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Assuming that shelter occupancy differs between day and night, not only season but also time of the day should influence the magnitude of interference between the bullhead and both goby species. Bottom-dwelling fishes such as bullheads and some Ponto-Caspian gobies are usually nocturnal, seeking a hiding place during the day and being most active at dusk or at night (Tomlinson and Perrow 2003;Erös et al 2005;Johnson et al 2008;Gaygusuz et al 2010;Grabowska et al 2016). On the other hand, shelter occupancy by the monkey goby did not differ between night and day, which corroborates the lack of a clear diel pattern of its foraging activity (Grabowska et al 2009).…”
Section: Discussionmentioning
confidence: 58%
“…This species reveals a morphological specialization for sandy substrata (Č ápová et al 2008), and in newly invaded ecosystems, it is often found on sandy bottom, e.g. in the Vistula River system (Danilkiewicz 1998;Kostrzewa and Grabowski 2002), Danube (Holčik et al 2003;Erös et al 2005;Polačik et al 2008) and Rhine (Borcherding et al 2011). Throughout the year, monkey gobies were caught usually on sand except for the spawning season when they occupied artificial shelters (Kakareko 2011).…”
Section: Introductionmentioning
confidence: 99%
“…(Eros et al, 2005;Harka and Biro, 2007) and in the lower Rhine (Borcherding et al, 2011). These low abundances imply a lower probability of being pumped up into the ballasts and thus may also explain why, conversely to the two other species, the Western tubenose goby would not have expanded through inland navigation.…”
Section: Figurementioning
confidence: 99%
“…This is unlikely, however, as it is more probable that the Slovak individuals are part of the same introduction into Austrian waters 50 km upstream (see Wiesner, 2005), probably via ship to the Viennese port of Hafen Lobau. This is all the more likely as, despite intensive sampling efforts, no specimens were caught along the Hungarian (Erös, 2005;Erös et al, 2005) or Slovak (Jurajda et al, 2005) …”
Section: > Racer Goby Babka Gymnotrachelus (Kessler 1857)mentioning
confidence: 99%